Non-native insect pests from the Madeira Archipelago (Portugal): new records and further data (Insecta: Orthoptera; Thysanoptera; Hemiptera; Coleoptera; Diptera; Lepidoptera; Hymenoptera) - Bella, Salvatore; Aguiar, Antonio Franquinho (Fragmenta entomologica, 2020)
In this study, the results of recent surveys on non-native insect pests from the Madeira Archipelago are reported. Overall, 13 non-native species were recorded: Tessellana tessellata (Charpentier) (Orthoptera, Tettigoniidae), Gynaikothrips ficorum (Marchal) (Thysanoptera, Phlaeothripidae), Leptoglossus occidentalis Heidemann (Hemiptera, Coreidae), Macrohomotoma gladiata Kuwayama (Hemiptera, Homotomidae), Platycorypha nigrivirga Burckhardt and Cacopsylla fulguralis (Kuwayama) (Hemiptera, Psyllidae), Greenidea ficicola Takahashi (Hemiptera, Aphididae), Aloephagus myersi Essig (Hemiptera, Pemphigidae), Protopulvinaria pyriformis (Cockerell) (Hemiptera, Coccidae), Rhynchophorus ferrugineus Olivier (Coleoptera, Dryophthoridae), Phytoliriomyza jacarandae Steyskal and Spencer (Diptera, Agromyzidae), Lantanophaga pusillidactylus (Walker) (Lepidoptera, Pterophoridae), and Josephiella microcarpae Beardsley and Rasplus (Hymenoptera, Agaonidae). Particularly, T. tessellata, L. occidentalis, M. gladiata, P. jacarandae, and J. microcarpae are reported for the first time from the island of Madeira. L. occidentalis is also reported for the first time from the island of Porto Santo. For P. jacarandae this is the first record from Macaronesia, while for M. gladiata this is the first record also for Portugal. Most of these species are associated with allochthonous plants. Details on current distributions, host plants, biological remarks, and natural enemies are given for each species.